KUALITAS PEMURNIAN VIRGIN COCONUT OIL (VCO) MENGGUNAKAN BEBERAPA ADSORBEN - Sangi, Meiske (Sam Ratulangi University, 2010)
ABSTRACTFatimah, F and M. Sangi, 2010. Purifying quality of virgin coconut oil using adsorbens.A Study has been carried out to know the influence of purification use some adsorben on quality of virgin coconut oil ( VCO). The adsorben where used was ash of paddy husk, active charcoal and natural zeolite. TheVCO quality measured by water and free fatty acid contents and peroxide number. The experimental result showed that the highest recovery was VCO that filtered use zeolite. Each type of adsorben gave the different influence to quality VCO. Ash of paddy husk represent the best adsorben in degrading water content (72,29 %) and free fatty acid (39,10 %), while natural zeolite represent the best adsorben in degrading number of peroxide VCO (74,549 %).Keywords : virgin coconut oil, adsorben, ash of paddy husk, active charcoal, zeolite